The influence of Islamic ethical return, investment and firm value - Febri, RS., Wahyu; Sagena, Basir (MEC-J (Management and Economics Journal), 2018)
An interest of investors in investing in the stock market is to get a rate of return as an element of revenue. Given this background, this study was to determine the influence of ethical Islamic return on investment and the value of the company, as well as the effect of the investment on firm value. The research was conducted on companies listed in the Jakarta Islamic Index for the period 2012-2015. The results showed an increase in income of non-kosher will lower interest of investors to invest, increase the amount of revenue non-kosher will lower the value of the company, an increase in the deviation of investment according to Islamic principles have a negative significant effect to company value, and increasing the amount of income halal through investments based on the principle of sharia will enhance shareholder value.Â